Gender differences in Salix myrsinifolia at the pre‐reproductive stage are little affected by simulated climatic change. Issue 4 (13th September 2012) - Nybakken, Line; Julkunen‐Tiitto, Riitta
<x xml:space="preserve">Abstract</x> Females of dioecious species are known often to prioritize defense, while males grow faster. As climatic change is known to influence both growth and defense in plants, it would be important to know whether it affects the sexes of dioecious species differently. This could have impacts on future sex ratios in nature. We grew four clones of each sex of Salix myrsinifolia in greenhouse chambers under ambient conditions, enhanced temperature, enhanced CO2 or enhanced temperature + enhanced CO2. The females had the greatest growth and also the highest levels of phenolic compounds in twigs, while in leaves some compounds were higher in males, some in females. Enhanced CO2 increased growth equally in both sexes, while growth was not affected by elevated temperature. Phenolic compounds in twigs were, however, lowered under elevated temperature. The gender differences were not strongly affected by the simulated climatic changes, but the effects seen on some highly concentrated compounds may be important. We interpret the intensive growth at pre‐reproductive phase as a strategy in females to get an initial advantage before later periods with fewer resources available for growth.